Irritation Test and Students’ Perception of Tobacco Extract Bar Soap (Nicotiana tabacum) Made from Cooking Oil Waste - Sandika, Bayu (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2023)
The purpose of this study was to analyze the irritation test and students' perceptions of the effects that might be caused by the use of tobacco extract bar soap made from waste cooking oil. The research was carried out in three stages, namely cleaning up cooking oil waste, making tobacco extract bar soap made from cooking oil waste, and clinical trials of soap on panelists. The results showed that the clarification of cooking oil waste succeeded in changing the concentrated cooking oil waste to a brighter color. The resulting tobacco extract soap made from cooking oil waste has a pH and water content according to the Indonesian National Standard (SNI) for bar soap. Clinical testing of the soap on 10 students showed that the tobacco extract soap did not cause significant irritation symptoms to the students' skin.